Associations between personality disorder characteristics and treatment outcomes in people with co-occurring alcohol misuse and depression. Issue 1 (December 2016) - McCarter, Kristen; Halpin, Sean; Baker, Amanda; Kay-Lambkin, Frances; Lewin, Terry; Thornton, Louise; Kavanagh, David; Kelly, Brian
Abstract Background Personality disorders are highly comorbid with alcohol misuse and depressive symptomatology; however, few studies have investigated treatment outcomes in this population. The aim of this study was to examine relationships between baseline personality disorder cluster profiles and overall and treatment-related changes for those with co-occurring alcohol misuse and depression. Methods Secondary analysis was conducted using a subset of data (N = 290) from two randomised controlled trials of psychological interventions for co-occurring alcohol misuse and depression, which did not specifically target personality disorders. Baseline dimensional personality disorder cluster scores were derived from the International Personality Disorder Examination Questionnaire (IPDEQ). Four treatment conditions were compared: a brief integrated intervention, followed by no further treatment, or nine further sessions of integrated-, alcohol-, or depression-focused treatment. Associations between IPDEQ scores and changes in alcohol use, depressive symptoms and functioning from baseline to the 6- and the 12-month follow-ups were of primary interest. Results Personality disorder cluster scores moderately negatively impacted on overall change (primarily Cluster C), as well as treatment-related outcomes (primarily Cluster A), particularly changes in depressive symptoms and psychosocial functioning. Longer interventions appeared to be more effective in the longer-term (e.g., at 12-month follow-up), with integrated interventions relatively more effective than single-focused ones for individuals with higher personality disorder cluster scores. Conclusions Greater attention needs to be paid to particular personality disorder clusters during the assessment and treatment of individuals with co-occurring alcohol misuse and depression. Integrated interventions, incorporating motivational interviewing and cognitive behaviour therapy, may provide a useful therapeutic framework. Integrated interventions also provide opportunities for adjunctive components focussing on other issues and coping strategies (e.g., to offset negative affective states), potentially tailored to the characteristics and needs of individual participants.